The legal and technical possibilities of using of scaffoldings as the ramp for disabled persons - Błazik-Borowa, Ewa; Pieńko, Michał; Robak, Aleksander (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The paper is devoted to the problems of legal and technical making the ramp for disabled persons with scaffolds. Scaffolding system components allow you to assemble a structure that serve as the ramp and fulfil the requirements of technical conditions. From a legal point the most important is the fact that the ramp construction needs a building application. In this regard, the greatest problems is obtaining the rights to use the property for construction purposes. A big challenge is to also perform stress analysis, taking into account of dynamic impacts caused by the movement of the trolley. In this regard, the paper presents a numerical model of the ramp, static analysis, modal analysis and results of prediction of a disabled person ride on the trolley. The results of computer calculations have shown that the construction of the ramp requires the exact numerical analysis. Therefore, the best option would be in order to scaffolding companies will prepare relevant technical documentation of products which are ramps for the disabled.